From words to worries: A cross-cultural comparison of parent-child conversations about snakes in early childhood - Reider Lori B.; Landry Yuan Félix; Leung Even Y.M.; Yeung Karen K.L.; Leung Samantha Hing Lam; Hai Catherine Wai Ching; Lei Janet Hiu Ching; LoBue Vanessa (PLoS ONE, 2026)
Fear of animals is shaped by psychological, cultural, and evolutionary influences over time. This study examined whether conversations about commonly feared animals—namely snakes—differ among parents and children from different cultures. Parents and children from the United States (n = 31; 28 Mothers, 2 Fathers, 1 Other; 15 Males, 16 Females, M age = 71.55 months, SD age = 12.56, Range age = 42) and Hong Kong (n = 31, 29 Mothers, 2 Fathers; 17 Males, 14 Females, M age = 76.48 months, SD age = 12.12, Range age = 44) read through a picture book of snakes, spiders, lizards, and turtles, and their conversations were coded for emotional content. Parents and children also completed several questionnaires, including a measure of their fear beliefs toward each animal. Parents and children across sites were more fearful of and used more negative language about snakes and spiders than lizards and turtles, and parents from Hong Kong expressed more fear and used more negative language about snakes than parents from the United States. However, despite more fear and negative language from Hong Kong parents, children from Hong Kong reported being less fearful of snakes (and spiders) than children from the United States, while Hong Kong children reported feeling more afraid of turtles and lizards. These findings highlight the prevalence of snake fears and negative information about snakes across different regions of the world, and potential differences in the kinds of input parents convey to children about snakes across cultures.